Cooperative Breeding in the Ambrosia Beetle Xyleborus affinis and Management of Its Fungal Symbionts - Biedermann, Peter H. W. (Frontiers in Ecology and Evolution, 2020)
Fungus-farming is known from attine ants, macrotermites and ambrosia beetles (Scolytinae, Platypodinae). Farming ant and termite societies are superorganismal and grow fungal cultivars in monocultures. Social organization of ambrosia beetle groups and their farming systems are poorly studied, because of their enigmatic life within tunnel systems inside of wood. Ambrosia beetle-fungus symbioses evolved many times independently in both the beetles and their fungal cultivars. Observations suggest that there is evolutionary convergence between these lineages, but also a high variation in the degree of sociality and the modes of fungiculture. Using a laboratory observation technique, I here tried to give insights into the social system and fungus symbiosis of the sugar-cane borer, Xyleborus affinis Eichhoff (Scolytinae: Curculionidae), a currently poorly studied ambrosia beetle. The study revealed a cooperatively breeding system characterized by delayed dispersal of adult daughters, alloparental brood care by larvae and adults, and about half of the totipotent adult daughters laying eggs within the natal nest. Most interesting, there was a tendency of egg-laying females to engage more commonly in mutually beneficial behaviors than non-egg-layers. Fungus gardens covering gallery walls composed of five different filamentous fungi. A Raffaelea isolate was predominant and together with an unidentified fungus likely served as the main food for adults and larvae. Three isolates, a Mucor, a Fusarium and a Phaeoacremonium isolate were most abundant in the oldest gallery part close to the entrance; Mucor, Fusarium and the Raffaelea isolate in diseased individuals. Additionally, there was correlative evidence for some fungal isoaltes influencing beetle feeding and hygienic behaviors. Overall, X. affinis is now the second ambrosia beetle that can be classified as a cooperative breeder with division of labor among and between adults and larvae.